Pengaruh Konsumsi Tuak Terhadap Kadar Asam Urat Pada Masyarakat Dewasa di Desa Jagaraga Timur - Ni Komang Juliantini; Fihiruddin Fihiruddin; Yudha Anggit Jiwantoro (Jurnal Analis Medika Biosains (JAMBS), 2022)
Tuak is a type of alcoholic drink made from palm sugar. Excessive consumption of tuak continuously can increase the levels of uric acid in the body. Uric acid is the end product of purine metabolism. This study aimed to determine the effect of tuak consumption of uric acid levels in the adult community in East Jagaraga Village. This research is an analytical observation using a cross-sectional approach. The sampling technique was a simple random sampling of 48 people, namely 24 adults that consumed tuak and 24 adults who did not consume tuak. Data analysis in SPSS used an independent sample t-test. The average uric acid levels in 24 respondents that consumed and did not consume tuak were 7.46 mg/dl and 4.92 mg/dl, respectively. The results show that there is an effect of tuak consumption uric acid levels in the adult community in the East Jagaraga Village, this is shown in a probability value (p = 0.000) <0.05 then Ho is rejected and Ha is accepted. From these results, it can be concluded that the consumption of tuak in the long term affects increasing uric acid levels.